Effects of fluids on microvascular perfusion in patients with severe sepsis (2010)
Purpose To evaluate the effects of fluid administration on microcirculatory alterations in sepsis. Methods With a Sidestream Dark Field device, we evaluated the effects of fluids on the sublingual microcirculation in 60 patients with severe sepsis. These patients were investigated either within 24 h (early, n = 37) or more than 48 h (late, n = 23) after a diagnosis of severe sepsis. Hemodynamic and microcirculatory measurements were obtained before and 30 min after administration of 1,000 ml Ringer’s lactate (n = 29) or 400 ml 4% albumin (n = 31) solutions.